Studies on the syntheses of some nitrogen heterocycles with a pyrrolidine ring system / Zurina Shaameri - Haji Shaameri, Zurina (2007)
In this study, 3-hydroxy-4-methylproline (Hmp) was chosen as the synthetic target due to its unique structure and its presence in a variety of biologically active natural products. This thesis has been divided into five main sections. Chapter one is are view of the syntheses of Hmp and its derivatives by different research groups. Chapter two consists of the retrosynthetic analysis of Hmp, whilst chapter three consists of our own synthetic work. Experimental details including the spectroscopic data are provided in chapter four, and finally, future works are recommended in chapter five. Our synthetic approach towards the synthesis of Hmp involved Dieckmann cyclisation of an intermediate diester, coupled from readily available glycine methyl ester and methyl malonate potassium salt. Dieckmann cyclisation of the diester then gave us the required pyrrolidinone ring template which is also known as the p,p-diketoester. Letting the p,p-diketoester undergo a series of successive chemical reactions, which include alkylation with different electrophiles, stereoselective ketone reduction, dimethoxy carbonylation ,dialkylation at C-3 position, acylation and alkylation at C-5 position, successfully furnished us with over 40 pyrrolidine type compounds in good to moderate yields. All these attempts were significant to investigate the efficiency of our proposed synthetic route. In this study, we managed to synthesize important intermediates of not only Hmp, 162, in 5 steps (with an overall yield of 26%) but also an Hmp-derivative, 170, in 7 steps (with an overall yield of 1.3%). It is also pleasing to note that three of our synthesized compounds were confirmed to exhibit neuroprotective ability via the hydrogen peroxide oxidative stress-induced model. In brief, a novel synthetic approach towards the syntheses of some pyrrolidine type compounds of biological importance was devised. Even though this approach can lead to the synthesis of Hmp, results extracted from this study thus far may be used to develop new scientific knowledge and remarkable findings.